2020
DOI: 10.1155/2020/4587459
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics in the Management of Atopic Dermatitis for Children: A Case-Based Review

Abstract: Background. Atopic dermatitis or eczema is one of the most common dermatologic problems, especially in children. Several studies have hypothesized that alteration of gut-colonizing microbes might have induced and conditioned the development of the disease. Thus, modulation of microbial diversity and abundance might help alleviate symptoms and conditions for patients. Given the ability of commensal and symbiotic microorganisms in modulating the immune system, probiotics administration has been studied in previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Fang et al [ 28 ] have focused on the the potential mechanisms of probiotics on alleviating AD via upregulation of epidermal barrier and regulation of immune signaling, and the possible effective substances on AD, which provide the supports for targeting gut microbiota to AD prevention and treatment. Disamantiaji et al [ 69 ] have included a total of 5 studies, and have concluded that probiotics supplementation in the management of eczema in children does not show a clinically relevant difference vs. standard treatment in reducing eczema severity. We focused on the relationship of gut microbiota and AD in the children population, with more studies included, we have found that probiotics may be an effective and safe treatment option for AD.…”
Section: Discussionmentioning
confidence: 99%
“…Fang et al [ 28 ] have focused on the the potential mechanisms of probiotics on alleviating AD via upregulation of epidermal barrier and regulation of immune signaling, and the possible effective substances on AD, which provide the supports for targeting gut microbiota to AD prevention and treatment. Disamantiaji et al [ 69 ] have included a total of 5 studies, and have concluded that probiotics supplementation in the management of eczema in children does not show a clinically relevant difference vs. standard treatment in reducing eczema severity. We focused on the relationship of gut microbiota and AD in the children population, with more studies included, we have found that probiotics may be an effective and safe treatment option for AD.…”
Section: Discussionmentioning
confidence: 99%